Chromosomal Instability May Not Be a Predictor for Immune Checkpoint Inhibitors from a Comprehensive Bioinformatics Analysis - Chiao-En Wu; Da-Wei Yeh; Yi-Ru Pan; Wen-Kuan Huang; Ming-Huang Chen; John Wen-Cheng Chang; Jen-Shi Chen; Yu-Chao Wang; Chun-Nan Yeh (Life, 2020)
Immune checkpoint inhibitors (ICIs) have become the standard of care in various cancers, although their predictive tools have not yet completely developed. Here, we aimed to exam the role of 70-gene chromosomal instability signature (CIN70) in cancers, and its association with previous predictors, tumor mutation burden (TMB), and microsatellite instability (MSI), for patients undergoing ICIs, as well as the possible predictive value for ICIs. We examined the association of CIN70 with TMB and MSI, as well as the impact of these biomarkers on the survival of 33 cancer cohorts from The Cancer Genome Atlas (TCGA) databank. The predictive value of the ICIs of CIN70 in previously published reports was also validated. Using the TCGA dataset, CIN70 scores were frequently (either positively or negatively) associated with TMB, but were only significantly associated with MSI status in three types of cancer. In addition, our current study showed that all TMB, MSI, and CIN70 had their own prognostic values for survival in patients with various cancers, and that they could be cancer type-specific. In two validation cohorts (melanoma by Hugo et al. and urothelial cancer by Snyder et al.), no significant difference of CIN70 scores was found between responders and non-responders (p-value = 0.226 and 0.108, respectively). In addition, no overall survival difference was noted between patients with a high CIN70 and those with a low CIN70 (p-value = 0.106 and 0.222, respectively). In conclusion, the current study, through a comprehensive bioinformatics analysis, demonstrated a correlation between CIN70 and TMB, but CIN70 is not the predictor for cancer patients undergoing ICIs. Future prospective studies are warranted to validate these findings.